Sustaining family institution: an Islamic perspective - Abd Malek, Normi (2011)
Islam views the family as a very important institution that should be protected from any element that may weaken it. If the institution cracks or is not stable, it will have a direct impact on society at large. The increase in social problems and criminal activities are among the direct results of unstable marriages. On the other hand, the trend to remain unmarried, avoiding family commitments, will also give a direct impact on the sustainability of the family institution. This paper highlights various safeguards that have been provided by Islamic law in order to ensure that the family institution is protected. The fact that Islam encourages marriage, prohibits celibacy and discourages divorce is highlighted. The roles of parties to the marriage as the key players, as well as the role of their family members in order to keep the marriage intact are examined. The paper also studies the three steps that should be taken by a husband as the leader of the family before resorting to divorce, as provided by the Quran. Finally, the role of the authorities in ensuring the sustainability of the family institution is analyzed.